Determinant of human capital disclosure in the post IFRS regime: an examination of listed firms in Nigerian / Mutalib Anifowose, Hafiz Majdi Ab. Rashid and Hairul Azlan Annuar - Anifowose, Mutalib; Ab. Rashid, Hafiz Majdi; Annuar, Hairul Azlan (Accounting Research Institute (ARI), Universiti Teknologi MARA (UiTM), 2017)
This paper examines the possible determinants of human capital disclosure among listed firms in Nigeria. This paper reports the results from a longitudinal panel data based on 442 observations of firms listed on the main board of Nigeria Stock Market for the period 2012-2014. The paper contributes to the literature by extending previous determinant of intangible asset disclosure studies by considering the Nigerian economics and business environment due to recent adoption of international financial reporting standards. Base on agency and proprietary cost theories, the study employs seven possible determinant of voluntary disclosure and developed checklist for human capital based prior studies. The results of longitudinal data analyses indicate a significant positive of firm's age, size and industry classification on human capital disclosure whereas the auditor's types, profitability, inherent risk and joint audit have significant negative influence of the of disclosure. The findings have practical implication for financial reporting council of Nigeria in developing HC disclosure standard and investors might utilise the findings in investment decision making process.